COVID-19 in the Shadows of MERS-CoV in the Kingdom of Saudi Arabia - Mazin Barry; Maha Al Amri; Ziad A. Memish (Springer, 2020)
Middle East Respiratory Syndrome Coronavirus (MERS-CoV) has plagued the Middle East since it was first reported in 2012. Recently, at the end of December 2019, a cluster of pneumonia cases were reported from Wuhan city, Hubei Province, China, linked to a wet seafood market with a new coronavirus identified as the etiologic agent currently named SARS-CoV-2. Most cases are in Mainland China with international spread to 25 countries. The novelty of the virus, the rapid national and international spread, and the lack of therapeutic and preventative strategies have led the WHO International Health Regulation emergency committee to declare the disease as Public Health Emergency of International Concern (PHEIC) on January 30, 2020. As it relates to countries with the ongoing MERS-CoV community cases and hospital acquired infections, there will be a huge challenge for HCWs to deal with both coronaviruses, especially with the lack of standardized and approved point of care testing. This challenge will now be faced by the whole global health community dealing with COVID-19 since both coronaviruses have similar presentation. Those patients should now be tested for both MERS-CoV and SARS-CoV-2 simultaneously, and with the continuing wide international spread of SARS-CoV-2, the travel history to China in the last 14 days will be of less significance